Thermal stresses in a box structure - Lempriere, B. M. (College of Aeronautics, 1958)
This interim note presents an analysis, using an energy method, of the thermal stresses in a finite length box structure resulting from uniform skin heating. The solution depends upon an eighth order differential equation with constant coefficients. Numerical solutions are given for comparison with existing and projected experiments